Inside Cover: Type II Intramolecular [5+2] Cycloaddition: Facile Synthesis of Highly Functionalized Bridged Ring Systems (Angew. Chem. Int. Ed. 6/2015). Issue 6 (7th January 2015) - Mei, Guangjian; Liu, Xin; Qiao, Chuang; Chen, Wei; Li, Chuang‐chuang
Abstract : Highly functionalized bridged ring systems can be prepared through a type II intramolecular [5+2] cycloaddition. In their Communication onpage 1754 ff., C.‐c. Li and co‐workers describe the efficient diastereoselective formation of synthetically challenging bicyclic cycloheptane skeletons, including the highly strained tricyclic cores of ingenol and cyclocitrinol. The Chinese water‐and‐ink painting in the background emphasizes the gaining of complex results from simple combinations.